Pathogenesis of Behçet's Syndrome: Genetic, Environmental and Immunological Factors - Mattioli, Irene; Bettiol, Alessandra; Saruhan-Direskeneli, Güher; Direskeneli, Haner; Emmi, Giacomo (Frontiers in Medicine, 2021)
Behçet's syndrome (BS) is a rare systemic vasculitis, characterized by a wide range of different clinical involvements and unpredictable phases of recurrence and remission. BS can be described as a multifactorial disease with an incompletely known etiopathogenesis; in fact, though presenting some peculiar features, such as its typical geographic distribution and the strong association with the well-known genetic predisposing factor HLA-B*51, the cause behind the onset and progression of the disease remains currently not fully understood. Besides genetic HLA and non-HLA predisposing associations and epigenetic influence, environmental factors also play an important role in the pathogenesis of the disease, and among these, infectious agents (both bacterial and viral) and specific microbiome alterations are considered of particular relevance in BS pathogenesis. BS has been included for decades among autoimmune diseases, in light of evidence showing T- and B-cell aberrant responses. However, because of recurrent mucocutaneous lesions and episodes of inflammation without antigen-specific T-cell or autoantibody responses, BS has also been classified among autoinflammatory disorders. Nevertheless, differently from autoinflammatory diseases, BS mildly responds to therapies targeting IL-1, its onset is not usually in childhood, and has high neutrophilic vasculitic involvement. Finally, given the association with HLA class I alleles, similar to spondyloarthropathies, the concept of BS as a major histocompatibility complex (MHC) I -opathy has been introduced. Understanding the complex etiopathogenesis of BS is essential to identify modifiable risk factors of BS occurrence or exacerbation and to develop targeted therapies. This review summarizes current evidence on the main genetic, environmental and immunological factors contributing to BS development.